Innovative Strategies for Hair Regrowth and Skin Visualization - Qiuying Mai; Yanhua Han; Guopan Cheng; Rui Ma; Zhao Yan; Xiaojia Chen; Guangtao Yu; Tongkai Chen; Shu Zhang (MDPI AG, 2023)
Today, about 50% of men and 15-30% of women are estimated to face hair-related problems, which create a significant psychological burden. Conventional treatments, including drug therapy and transplantation, remain the main strategies for the clinical management of these problems. However, these treatments are hindered by challenges such as drug-induced adverse effects and poor drug penetration due to the skin's barrier. Therefore, various efforts have been undertaken to enhance drug permeation based on the mechanisms of hair regrowth. Notably, understanding the delivery and diffusion of topically administered drugs is essential in hair loss research. This review focuses on the advancement of transdermal strategies for hair regrowth, particularly those involving external stimulation and regeneration (topical administration) as well as microneedles (transdermal delivery). Furthermore, it also describes the natural products that have become alternative agents to prevent hair loss. In addition, given that skin visualization is necessary for hair regrowth as it provides information on drug localization within the skin's structure, this review also discusses skin visualization strategies. Finally, it details the relevant patents and clinical trials in these areas. Together, this review highlights the innovative strategies for skin visualization and hair regrowth, aiming to provide novel ideas to researchers studying hair regrowth in the future.